Etika Persaingan dalm Bisnis Islam - Wahyudin Maguni (Institut Agama Islam Negeri (IAIN) Kendari, 2009)
Such as having comprehended that business ethics is applying of moral standard or values in morality and character of business which the was applying of will be able to improve long-range profitability and obtained will good of image of the positive of business which runs.In company business context, applying of business ethics confronted with problems covering process, people, and technology. Facing the reality, there are choices the confronted [is] to choose among four choices. Fourth of that condition is; a). Ethical otherwise hence dropping behind, b). Ethical does not drop behind, c). Etis drop behind, and d). no ethical drop behind.